The concept of “optimization” in political and managerial discourse - Ohanisian , Mykhailo; Kovtun, Yuliia (Theory and Practice of Public Administration, 2019)
The article is devoted to the research of optimization and improvement of the system of public administration in the present conditions, special attention is paid to the study of optimization as a method for increasing the efficiency of functioning of state authorities in Ukraine, analyzed research on optimization, as well as the current legislation of Ukraine on this issue, improving the quality of legal regulation of distribution functions in the public administration apparatus.Formulation of the problem: Many issues of modernization and optimization of the system of public authorities have already been reflected in many articles of Ukrainian scholars. In today's conditions of socio-political and economic life, an important role should be played by the introduction of optimization mechanisms in the activities of public authorities. One of such mechanisms should be the modernization methods of strategic integration between public authorities regarding the adoption and implementation of joint state and management decisions. In recent years, new values and a new model of culture in state bodies have emerged in Ukraine. The tasks of the modern stage of the development of the state administration system are due to the accelerated social modernization of Ukrainian society, which faces the task of getting rid of false social indicators.We can note that the functional structure of public administration in Ukraine still needs theoretical development, improvement of tools and introduction of new methods - a qualitatively new approach, a new methodology is needed.Based on this, we identified the problem of this study:- a real contradiction that requires its solution: between the urgent need for a scientifically sound organization of the process of activity, tasks and functions of public administration with a view to optimizing them, starting with central state bodies (and their structural divisions) and ending with the bodies of local self-government (and their structural subdivisions )- the imperfection of the methodology of optimizing the tasks and functions of state bodies used in Ukraine today, the impossibility of its effective application in the conditions of qualitative complication of the system of public administration, conditioned by the reform of local self-government.Analysis of recent research and publications. In the dissertation study by V. Malinovsky "Optimization of the Functions of the Executive Bodies of Ukraine: Theoretical and Methodological Foundations", the problem of defining the concept of "optimization" and the peculiarities of its application in relation to the system of state authorities took up a significant place. In addition, the researcher notes that the lack of development of this scientific problem significantly restrains the implementation of functional and structural reforms of the executive power, deprives the political-managerial activities of the necessary organizing and efficiency.For the first time in the field of jurisprudence optimization in the framework of his dissertation research was investigated by Y.L. Vlasenko, in the context of the instrument for improving a separate sphere of legislation of Ukraine, in particular, ensuring the ecological safety of Ukraine.Also, the issue of optimization in relation to improving the activities of public authorities in Ukraine was investigated in the works of L. E. Kisil.The authors of the monograph "Administrative Reform in Ukraine: Current State, Problems and Prospects" state that one of the reasons for delaying the reform of public administration is the lack of elaboration of individual problems, the permanent search for an optimal model for the organization of public administration.The purpose of the article. The process of optimizing social activities is directly related to management and, therefore, penetrates all other activities, specifying and acquiring unique features. In the current literature, many works are devoted to the optimization of specific activities, natural, technical, and economic aspects, but only recently, the process of optimization has been considered as an independent research object. The problem of optimization and optimality is extremely multifaceted.In the study of the problems of optimizing public administration, it is expedient to use the definition of the system as a holistic entity with new integrated qualities that are not specific to its components separately, but arose due to their interaction.One of the main features of public authorities in general and in particular executive bodies is systematic. The system of executive bodies is a collection in which all components, namely, separate bodies and their structural subdivisions, are interconnected and at the same time constitute independent subsystems with their specific features of structure, functions and competencies. Taking into account such criteria as: scope of competence and territorial scope of government activities. The system and subsystems of executive bodies have, respectively, organizational structures that reflect the interrelations between the individual links of the system and subsystems. The optimality of the organizational structures of this system is one of the factors of increasing the efficiency of the authorities.In optimizing the system of public administration in the conditions of democratization of public relations, we consider it worth to understand - the purposeful process of achieving the maximum possible value of the effectiveness of the system of public administration for the minimum value of the quality of functioning of such a system in terms of redistribution of political power, with due regard to the need for the delegation of power to other sub rights, in particular directly to civil society institutions. It is generally recognized that without the improvement of the territorial organization of the state, to build a fundamentally new system of public administration in it is impossible.Conclusions and perspectives of further research. We believe that optimization of public administration in Ukraine is extremely necessary. However, there is no doubt that optimization should be balanced, justified from the standpoint of practice, taking into account comments and suggestions. Optimization will bring the system of public authorities to a state that would enable the most efficiently to carry out its tasks, functions, and provide administrative services. And in the first place, it is necessary to improve the normative regulation of the organization and order of the activities of public authorities.Thus, our theoretical and methodological analysis of the concept of optimization in political and managerial discourse, made possible to reveal the essence of optimization in the activities of public authorities as one of the forms of coordinated interaction of state-management structures, which is aimed at ensuring the effectiveness of the implementation of the corresponding organizational functions.